2022
DOI: 10.2106/jbjs.22.00648
|View full text |Cite
|
Sign up to set email alerts
|

Hip Displacement After Triradiate Cartilage Closure in Nonambulatory Cerebral Palsy

Abstract: Background:Recommendations with regard to the need for continued hip surveillance after skeletal maturity are based on expert opinion rather than evidence. This study aimed to determine the prevalence of and risk factors associated with progressive hip displacement in cerebral palsy (CP) after triradiate cartilage (TRC) closure.Methods:Patients who had spastic nonambulatory CP (Gross Motor Function Classification System IV to V) and hypertonic (spastic or mixed-type) motor type and follow-up of at least 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
(47 reference statements)
0
10
0
1
Order By: Relevance
“…It has been assumed that the risk of progressive HD is negligible after triradiate cartilage (TRC) closure—a proxy for the onset of skeletal maturity—and thus HS could safely be discontinued after that point [ 9 ]. A recent large study, however, has demonstrated that there is a risk of further hip displacement in children with CP after closure of the TRC especially for those with risk factors including male gender, pelvic obliquity, high MP and no prior surgery [ 40 ]. For those youth at risk, the authors suggested that HS be continued up until age 18 years, with at least an x-ray every 2 years [ 40 ].…”
Section: Knowledge Gaps With Respect To Hip Surveillancementioning
confidence: 99%
See 4 more Smart Citations
“…It has been assumed that the risk of progressive HD is negligible after triradiate cartilage (TRC) closure—a proxy for the onset of skeletal maturity—and thus HS could safely be discontinued after that point [ 9 ]. A recent large study, however, has demonstrated that there is a risk of further hip displacement in children with CP after closure of the TRC especially for those with risk factors including male gender, pelvic obliquity, high MP and no prior surgery [ 40 ]. For those youth at risk, the authors suggested that HS be continued up until age 18 years, with at least an x-ray every 2 years [ 40 ].…”
Section: Knowledge Gaps With Respect To Hip Surveillancementioning
confidence: 99%
“…A recent large study, however, has demonstrated that there is a risk of further hip displacement in children with CP after closure of the TRC especially for those with risk factors including male gender, pelvic obliquity, high MP and no prior surgery [ 40 ]. For those youth at risk, the authors suggested that HS be continued up until age 18 years, with at least an x-ray every 2 years [ 40 ].…”
Section: Knowledge Gaps With Respect To Hip Surveillancementioning
confidence: 99%
See 3 more Smart Citations